Resepsi Teks dan Transformasi Kebudayaan - Agus Iswanto (Manuskripta, 2016)
Stuart Robson (Editor and Translator), The Kakawin Ghaṭotkacâśraya by Mpu Panuluh. Tokyo: Research Institute for Languages and Cultures of Asia and Africa, Tokyo University of Foreign Studies 2016.